Turnover time in the pandemic era: : industrial poultry, avian influenza and capitalist strategies - Jakobsen, Jostein; Barbesgaard, Mads; Aguilar-Støen, Mariel (Journal of Peasant Studies, 2025)
Focusing on mounting challenges to agro-industrial capitals posed by emerging infectious diseases, this paper revisits longstanding debates in critical agrarian studies scrutinizing the role of turnover time. Analyzing Norway and Denmark's poultry industries' recent confrontations with avian influenza, and by paying close attention to the questions of temporality and disaggregating the agency of capital, we elucidate the implicated classes of poultry capital along the broiler supply chain and their strategies in responding to differentiated challenges from avian influenza. In so doing, we argue for the relevance of conceptual tools derived from the under-acknowledged second volume of Marx's Capital.